Wujud dan Makna Implikatur dalam Humor Miss Dakem Karawang serta Alternatifnya sebagai Bahan Ajar Teks Anekdot di SMA Kelas X - Ria Sonia; Oding Supriadi; Sahlan Mujtaba (Silampari Bisa: Jurnal Penelitian Pendidikan Bahasa Indonesia, Daerah, dan Asing, 2021)
This study aims to describe the form and meaning of implicatures in Miss Dakem Karawang's humor. The type of research used in this research is descriptive qualitative. The subject of this research is the humorous utterances of Miss Dakem Karawang. Meanwhile, the object of this research is the form and meaning of implicature in Miss Dakem Karawang's humor. This research data collection was carried out by means of documentation, namely listening techniques, noting important things using data tables. This technique is done by listening carefully to a speech in the Miss Dakem Karawang humor video. Miss Dakem Karawang humor has 1 form of implicature and produces 9 conversational utterances. As for the meaning of implicature in this study, there are 5 meanings, namely, assertive, directive, commissive, expressive, and declarative, there are 12 conversational utterances containing implicature meaning in Miss Dakem Karawang. The results of this study are expected to be used as teaching materials for anecdotal texts in the form of handouts.